Explaining academic career success through self-efficacy, job satisfaction, and professional networking: A moderated mediation model - Data, Muhammad Umar; Haerani, Siti; Upe, Jusni Ambo; Muis, Mahlia (Edelweiss Applied Science and Technology, 2026)
Drawing upon Social Cognitive Career Theory (SCCT), this study examines the effects of self-efficacy, job satisfaction, and professional networking on lecturer performance and career success in private higher education institutions in Makassar. It also investigates the mediating role of lecturer performance and the moderating role of perceived organizational support. A quantitative research design was employed using survey data from 357 lecturers, which were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that self-efficacy, job satisfaction, and professional networking significantly enhance lecturer performance, which, in turn, positively influences career success. Lecturer performance also mediates the relationships between these antecedent variables and career success. However, perceived organizational support does not significantly moderate the relationship between lecturer performance and career success. These findings suggest that personal capabilities, psychological factors, and professional relationships play a more critical role in academic career success than organizational support. This study extends SCCT by emphasizing the importance of personal agency and social capital in academic career development. Practically, the findings provide guidance for higher education institutions in designing strategies to strengthen lecturer performance, foster professional networking, and promote sustainable career development.